Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species - Li, Yang; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2016)
Four subgenera of the genus Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) are newly reported to China, i.e., Ophthalmobracon Tobias, 1957; Orientobracon Tobias, 2000; Punctobracon Papp, 1996; and Sculptobracon Tobias, 1961. Six species are recognized, including five new species, B. (Ophthalmobracon) elevatus sp. nov., B. (Orientobracon) maculaverticalis sp. nov., B. (Orientobracon) laticanaliculatus sp. nov., B. (Punctobracon) rhyacioniainus sp. nov. and B. (Sculptobracon) obsoletus sp. nov., which are described and illustrated. Keys to the newly recorded Chinese subgenera and species are provided.